Use of Remifentanil in a Novel Clinical Paradigm to Characterize Onset and Duration of Opioid Blockade by Samidorphan, a Potent μ-Receptor Antagonist. Issue 3 (June 2015) - Shram, Megan J.; Silverman, Bernard; Ehrich, Elliot; Sellers, Edward M.; Turncliff, Ryan
Abstract : Abstract: A novel clinical study design was used to evaluate the blockade of a selective short-acting μ-opioid agonist (remifentanil) in 24 opioid-experienced subjects. Samidorphan (3-carboxamido-4-hydroxynaltrexone) is a novel opioid modulator with μ-antagonist properties. Objective (pupil diameter) and subjective (visual analog scale) responses to repeated remifentanil and saline infusion challenges were assessed after single oral administration of placebo (day 1) and samidorphan (day 2). Complete blockade persisted with samidorphan for 24 hours for pupil miosis and 48 hours for the drug liking visual analog scale. Samidorphan effects persisted beyond measurable samidorphan exposure ( t ½ = 7 hours). Samidorphan was associated with complete blockade of remifentanil, and the duration supports daily administration. This study used a novel approach with multiple administrations of remifentanil to successfully demonstrate a durable effect with samidorphan and a rapid and potent blockade of physiological and subjective μ-opioid effects.